The stress of anonymous online reviews: a conceptual model and research agenda. Issue 5 (13th July 2015) - Bradley, Graham L.; Sparks, Beverley A.; Weber, Karin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The paper aims to examine the impact of customer-generated negative online reviews on hospitality employees and businesses. It introduces the concept of negative online review stress, or NOR_Stress (occupational stress due to being targeted by negative online reviews), and present strategies for researching and managing the impact of negative online reviews. Design/methodology/approach – This conceptual paper sets forth a framework, based on the stress, services and hospitality literature, within which negative online reviews, NOR_Stress, and their impact on individuals and businesses can be understood. Aspects of the framework are illustrated by application of online archival material. Findings – The paper demonstrates how negative online reviews can have adverse and diverse effects on restaurant industry employees and businesses. Research limitations/implications – The paper sets out a research agenda relating to negative online reviews and NOR_Stress causes, consequences and countermeasures. Multiple research questions are posed, to be investigated through a combination of qualitative, survey and experimental methods. Practical implications – Four types of countermeasures are presented: preventative, protective, positive and palliative. Social implications – Negative online reviews can exact a hefty toll, potentially resulting not only in reduced customer patronage and company profitability but also in human and social consequences in the form of adverse stress reactions, loss of face and damaged personal and professional relationships. Originality/value – Negative online reviews have proliferated over the past decade and will continue to grow. This paper is the first to critically examine the human and business impacts of this growing threat to the hospitality industry.